Evolution of mosses according to biflavonoid and triflavonoid composition: Prelirninary considerations - LÓPEZ-SÁEZ, J. A.; P ÉREz-ALONSO, J. M.; VELASCo-NEGUERUELA, A. (Ars Pharmaceutica (Internet), 1996)
In this work we confirm that mosses are not primitive embryo-plants. They are crelated to vascular plants, according to their biflavonoid and triflavonoid composition.